Chinese Operations of Audit Committee and Supervisory Board - lee, paochen (Archives of Business Research, 2019)
Imposing the mechanism of a single audit committee (AC) on the dual supervisory mechanism of a Board of Directors alongside a supervisory board (SB) has raised questions regarding the problems in implementing effective monitoring. How the SB and the AC operated in a Chinese listed company is documented in this article by interviewing the secretary of BoD; the SB chairmen and an AC member. The issues rose in the interview point out the problems and evidences presented provide useful guidelines of how key characteristics of effectiveness and co-ordination can be improved to make supervisory functions in China more effective.